PENGARUH TEMPERATUR EKSTRUSI TERHADAP SIFAT FISIS, KIMIAWI DAN KEKUATAN TARIK FILAMEN ULTRA HIGH MOLECULAR WEIGHT POLYETHYLENE (UHMWPE) - Candra Irawan; Budi Arifvianto; Muslim Mahardika (P3M Politeknik Negeri Indramayu, 2021)
Currently, fused deposition modeling (FDM) has become a popular 3D printing technique for the fabrication of polymeric parts. In this technique, a polymer filament is melted and deposited layer-by-layer to form 3-dimensional objects. However, there are still limited number of polymer types that has been successfully used as a raw material for the FDM process. Up to now, there is still no filament made from ultra high molecular weight polyethylene (UHMWPE) available in the market. Therefore, a preliminary study concerning the fabrication of such UHMWPE filament needs to be conducted. In this study, the influence of extrusion temperature used in the fabrication of UHMWPE filament on the physical, chemical, and tensile strength of such filament was studied. The extrusion process was carried out by adding polyethylene glycol (PEG) and paraffin oil (PO) to improve the processability of UHMWPE material and with temperatures of 160 oC, 170 oC, and 180 °C. The result of examination by using electron microscope revealed that extrusion process of this polymer was running stable. The characterization by using differential scanning calorimetry (DSC) indicated a decrease in the degree of filament crystallinity as the extrusion temperature decreased. The characterization by using Fourier-transform infrared spectroscopy (FTIR) indicated no changes in the chemical compositions over the filament products with the increasing extrusion temperature applied. Meanwhile, it is also indicated from this study that the maximum tensile strength decreased as the extrusion temperature got lower. In this case, the highest maximum tensile strength could be achived by the UHMWPE filament extruded with temperature of 180 °C, i.e., with an average tensile strength of 22.52 MPa.